Integrated transcriptomic and proteomic characterization of a chromosome segment substitution line reveals a new regulatory network controlling the seed storage profile of soybean. (24th March 2022) - Han, Xue; Li, Jiapeng; Zhao, Yabin; Zhang, Zhanguo; Jiang, Hongwei; Wang, Jinxing; Feng, Xuezhen; Zhang, Yu; Du, Ziyue; Wu, Xiaoxia; Chen, Qingshan; Qi, Zhaoming
Abstract: Soybean is a major crop that provides oil and protein worldwide. Soybean products have been consumed for centuries in many different kinds of food. The regulatory network that controls the accumulation of fatty acids (FAs) and storage proteins (SSPs) in seeds is poorly understood. To gain new insights into the molecular mechanisms that contribute to high‐quality seeds, seed FA and SSP contents were analyzed for the effects of chromosome segment substitution in a wild soybean line (CSSL). High‐throughput transcriptomics and tandem mass tag (TMT)‐based quantitative proteomics were performed on the dry seeds of the CSSL and parent lines. In total, 665 differentially expressed genes (DEGs) and 83 differentially accumulated proteins (DAPs) were identified. Of these 27 DEGs and 23 DAPs were found to regulate the seed storage profile. These genes encode proteins involved in photosynthesis, protein processing, protein sorting, and storage protein accumulation. Data are presented showing that FA synthesis was decreased by the regulation of SSP‐accumulation‐related genes and proteins. Taken together, the results provide new insights into the regulation network involved in the accumulation of seed storage compounds involving both source and sink processes that may be used as markers in future soybean breeding programs. Abstract : A CSSL had higher SSP and lower FA seed contents than the recurrent parent SN14. Analysis of integrated RNA‐seq and TMT‐based proteome data revealed key DEGs and DAPs. Major DEGs and DAPs were associated with SSP accumulation and FA degradation pathways. A regulatory network underlying source‐to‐sink soybean seed storage was identified.